Reformasi Implementasi Konsep Blue Economy sebagai Upaya Proteksi Kesejahteraan Masyarakat Pesisir Kota Semarang - Aulia Audrey Al Fahri; Dinda Norrahmawati; Kevin Daru Bailovan; Rifky Usman Alfarez; Sekar Alifia Rahmawati; Kismartini Kismartini; Hartuti Purnaweni (Jurnal Manajemen dan Ilmu Administrasi Publik (JMIAP), 2022)
The purpose of this research is to find out the implementation of the blue economy concept and the role of stakeholders in it in the maritime area of Semarang City. In this study using a descriptive qualitative approach. Data collection techniques through library research in the form of research documents, journal publications, and government website data. The results of the study concluded that the strategy for implementing the blue economy in the city of Semarang is by utilizing technology to maximize aquaculture and trade in the coastal areas of Semarang city. Furthermore, the role of inter-stakeholders needs to be maintained in synergy to achieve maximum results later.